OPTICAL COHERENCE TOMOGRAPHY IN JUVENILE NEURONAL CEROID LIPOFUSCINOSIS - Hansen, Michael S. (Retin Cases Brief Rep, 2016)
PURPOSE: To report optical coherence tomography findings obtained in two patients with juvenile neuronal ceroid lipofuscinosis. METHODS: Two case reports. RESULTS: Two 7-year-old girls presented with decreased visual acuity, clumsiness, night blindness, and behavioral problems. Optical coherence tomography showed an overall reduction in thickness of the central retina, as well as the outer and the inner retinal layers. The degenerative retinal changes were the same, despite different mutations in the CLN3 gene. CONCLUSION: In these rare cases of juvenile neuronal ceroid lipofuscinosis, optical coherence tomography enabled unambiguous detection of prominent morphologic abnormalities of the retina at the patient's first presentation. The advanced stage of photoreceptor degeneration seen in our patients shows that a diagnosis can potentially be made much earlier.